Bereavement stressors and psychosocial well-being of young adults following the loss of a parent – A cross-sectional survey. (August 2018) - Lundberg, Tina; Forinder, Ulla; Olsson, Mariann; Fürst, Carl Johan; Årestedt, Kristofer; Alvariza, Anette
Abstract: Purpose: The knowledge about young adults who have lost a parent to cancer is limited, and to reach a broader understanding about this group, this study used the Dual Process Model of Coping with Bereavement (Stroebe and Schut, 1999) as a theoretical framework. The purpose of this study was to describe loss- and restoration-oriented bereavement stressors and psychosocial wellbeing of young adults following the loss of a parent to cancer. Method: This survey used baseline data from a longitudinal study. Young adults, aged 16–28 years, who lost a parent to cancer more than two months earlier and agreed to participate in support groups held at three palliative care services in Sweden, responded to a comprehensive theory-based study-specific questionnaire. Results: Altogether, 77 young adults (64 women and 13 men) answered the questionnaire an average of five-to-eight months after the loss. Twenty percent ( n = 15) had not been aware of their parent's impending death at all or only knew a few hours before the death, and 65% ( n = 50) did not expect the death when it occurred. The young adults reported low self-esteem ( n = 58, 76%), mild to severe anxiety ( n = 55, 74%), mild to severe depression ( n = 23, 31%) and low life satisfaction. Conclusion: Young adults reported overall poor psychosocial wellbeing following bereavement. The unexpectedness and unawareness of the parent's imminent death, i.e., loss-oriented bereavement stressors, might influence psychosocial wellbeing. Despite these reports, restoration-oriented stressors, such as support from family and friends, helped them to cope with the loss. Highlights: Young adults had poor psychosocial wellbeing following parental bereavement. Low self-esteem, anxiety, depression and low life satisfaction was reported. The expectedness of a parent's imminent death was low. Many received support from family and friends and believed in a meaningful future.